(untitled) (Avocetta, 2016)
The Audouin’s Gull Larus audouinii Payraudeau, 1826 has never been recorded breeding in Sicily: the authors are here reporting the discovery of a breeding colony on the island of Vendicari, province of Siracusa, off the south-east coast of Sicily. An estimated 50 60 pairs have bred there in 2010 and 2011 and 100 to 130 pairs in the period 2012-2016. All the basic information on breeding attempts and success, egg-laying dates, number of eggs laid, number of chicks fledged, and characteristics of each nest was collected. During the breeding season of 2012-2016 a total of 19 ringed adults were observed at the colony: 11 of these originated from the same colony (Vendicari) while 8 came from other colonies, of which 6 from Italy and 2 from the Ebro delta in Spain. Those gulls ringed as chicks from the Vendicari colony have so far shown that they spend the winter months in Sicily and North Africa, while in the spring and summer months, these birds have been observed in Sicily, Calabria, Apulia and Campania. The data presented here demonstrate the ability of this species in occupying new territories, sometimes on the periphery, and a tendency of population increase in a very short period of time, presumably through recruitment of individuals originating from other colonies. The data collected confirm a strong nest-site tenacity and also show that a significant part of the individuals present in the colony consisted of birds in their third year of life.